Satisfacción del cliente en el Servicio Técnico Ghost Solutions del cantón Babahoyo periodo 2023. - Ramírez Millán, Lilibeth Mariela (2024)
This case study is based on the analysis of customer satisfaction in the Ghost Solutions Technical Service, a company dedicated to the sale of phone accessories and technical services for the repair and maintenance of electronic devices, through research techniques, to promote loyalty and improve reputation. As an important point for the execution of this case study, the little attention given to customer satisfaction by the employees of this company was taken into account, which is why we seek to analyze what are the fundamental aspects that are affecting the company. and at the same time its evaluation. To carry out this case study, root-cause analytical research methods were applied. This approach facilitated the determination of the factors that affect the customer satisfaction process, allowing us to understand at the same time the origin of the difficulties, through carrying out a basic technique such as a survey directed at customers, taking into account key assessment points that were evaluated through a questionnaire, in order to carry out a clear analysis of customer satisfaction after their purchase or acquisition of a service of repair and at the same time promote the implementation of strategies that improve these shortcomings.